2016
DOI: 10.1007/s00520-016-3221-3
|View full text |Cite
|
Sign up to set email alerts
|

Unmet care needs in people living with advanced cancer: a systematic review

Abstract: PURPOSE:\ud The support needs of cancer patients vary according to the phase of their cancer journey. Recent developments in healthcare are such that the advanced cancer phase is increasingly experienced as a chronic illness phase, with consequent changes in patient support needs. Understanding these needs, and identifying areas of unmet need, can enable us to develop services that are more adequate to the task of supporting this population.\ud METHODS:\ud We conducted a systematic search of four electronic da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
135
0
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 144 publications
(150 citation statements)
references
References 44 publications
9
135
0
6
Order By: Relevance
“…Sexuality was the least‐common unmet need compared with the other 4 needs. This accords with previous reviews examining prevalence of unmet needs in cancer patients . A systematic review found that 7.4% of cancer population reported unmet sexuality needs, whereas 12.8% to 33.3% reported other types of unmet needs .…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Sexuality was the least‐common unmet need compared with the other 4 needs. This accords with previous reviews examining prevalence of unmet needs in cancer patients . A systematic review found that 7.4% of cancer population reported unmet sexuality needs, whereas 12.8% to 33.3% reported other types of unmet needs .…”
Section: Discussionsupporting
confidence: 89%
“…For example, a recent cross‐sectional study in Malaysian breast cancer patients found that the most prevalent types of unmet needs were uncertainty about future, fears about cancer spreading, and sadness . Yet such an approach focusing on prevalence of unmet needs at the group level could be misleading, making it difficult to consider individual differences on unmet needs . For example, a low‐frequency unmet need could be highly salient and clinically relevant for people who are experiencing that need …”
Section: Introductionmentioning
confidence: 99%
“…A systematic review estimated the prevalence of unmet needs among advanced cancer survivors (Moghaddam et al, 2016). The authors identified 23 studies (four qualitative) and found that a substantial percentage (ranging from 17% to 48%) of advanced cancer survivors experience psychological (fear of disease progression, pain, worry about others), physical (lack of energy, pain) and functional (managing activities of daily living) as well as sexual and spiritual needs that go unmet.…”
Section: Unmet Needs Of Advanced Cancer Survivorsmentioning
confidence: 99%
“…A recent scoping review of studies on self-management strategies and SMS needs of patients with advanced cancer found that patients engaged in a variety of self-management behaviours and have an extensive need for SMS (Budhwani et al, 2019). Patient needs for SMS fell broadly within the domains of managing complex, cyclical and chronic symptoms and the impact of those symptoms on the psychosocial aspects of daily life, findings supported by two systematic reviews of the unmet needs of people living with advanced cancer (Moghaddam, Coxon, Nabarro, Hardy, & Cox, 2016;Wang et al, 2018). The importance of the role of carers in addressing the self-management needs of patients with advanced cancer has also been highlighted (Budhwani et al, 2019), with managing patients' emotions identified as a particularly challenging part of caregiving (Wang et al, 2018).…”
mentioning
confidence: 96%
“…The needs of patients living with cancer that is treatable but incurable can resemble needs of patients with other chronic illness conditions (Moghaddam et al, 2016), and indeed, many may be managing other conditions in addition to cancer. The chronic condition literature reports increasing evidence that supporting people to manage their own health has positive outcomes, such as improved quality of life and reduced use of health services (de Longh, Petrea, Fenner, & Kidd, 2015).…”
mentioning
confidence: 99%